Timing of birth: Parsimony favors strategic over dysregulated parturition. Issue 1 (21st May 2015) - Catalano, Ralph; Goodman, Julia; Margerison‐Zilko, Claire; Falconi, April; Gemmill, Alison; Karasek, Deborah; Anderson, Elizabeth
Abstract : Objectives: The "dysregulated parturition" narrative posits that the human stress response includes a cascade of hormones that "dysregulates" and accelerates parturition but provides questionable utility as a guide to understand or prevent preterm birth. We offer and test a "strategic parturition" narrative that not only predicts the excess preterm births that dysregulated parturition predicts but also makes testable, sex‐specific predictions of the effect of stressful environments on the timing of birth among term pregnancies. Methods: We use interrupted time‐series modeling of cohorts conceived over 101 months to test for lengthening of early term male gestations in stressed population. We use an event widely reported to have stressed Americans and to have increased the incidence of low birth weight and fetal death across the country—the terrorist attacks of September 2001. We tested the hypothesis that the odds of male infants conceived in December 2000 (i.e., at term in September 2001) being born early as opposed to full term fell below the value expected from those conceived in the 50 prior and 50 following months. Results: We found that term male gestations exposed to the terrorist attacks exhibited 4% lower likelihood of early, as opposed to full or late, term birth. Conclusions: Strategic parturition explains observed data for which the dysregulated parturition narrative offers no prediction—the timing of birth among gestations stressed at term. Our narrative may help explain why findings from studies examining associations between population‐ and/or individual‐level stressors and preterm birth are generally mixed. Am. J. Hum. Biol. 28:31–35, 2016. © 2015 Wiley Periodicals, Inc.